Restrukturyzacja zadłużenia gminy z wykorzystaniem leasingu zwrotnego - Zarzecki, Dariusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The amount of debt in a number of local governments in Poland has achieved a dangerous level. This situation may result in bankruptcy of many local governments, as it happened in Brzozie. Insolvency threatens about 20 local governments in Poland.One of the possible ways of reducing debt of local governments is a sale and lease back transaction. The paper presented the key features of the sale and lease back agreements, and exhibited a practical concept of applying such a financial tool in decreasing debt in the local governments. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 453-461